SEIRS Type Mathematical Model Simulation (COVID19 Case) - Asmaidi As Med; Taqriri Kamal Mulyadi; Desi Febriani Putri; Rinancy Tumilaar (LPPM Politeknik Aceh Selatan, 2023)
Indonesia is one of the countries hit by COVID19 cases. Data shows that from January 2023 to May 2023, COVID19 cases are still sweeping Indonesia. Data on COVID19 cases in Indonesia on May 30, 2023 showed that 541 patients were confirmed positive with 8 deaths. The data shows that this COVID19 case still needs to be taken seriously and a solution is found. In this study, the authors developed a mathematical model of the spread of COVID19 cases. The mathematical modeling developed is a mathematical model of type SEIRS. In the SEIRS type mathematical model there are four populations including vulnerable population (S), latent population (E), infection population (I), and cured population (R). In the model, it is assumed that the cured population does not recover permanently, but can again suffer from COVID19 caused by other types of viruses. The purpose of developing a mathematical model of the SEIRS type is to determine the behavior of the population in the compartment diagram. Population behavior can be determined by simulating each population in the model. The simulation is performed when the value of the base reproduction number is less than zero and more than zero. Based on the simulations conducted showed that at the time of , the number of latent populations and infections decreased towards zero, while at the time of , latent population and infection still remained in the model so that the disease did not disappear.